Solution processed MoS2-PVA composite for sub-bandgap mode-locking of a wideband tunable ultrafast Er:fiber laser - Zhang,M; Howe,RCT; Woodward,RI; Kelleher,EJR; Torrisi,F; Hu,G; Popov,SV; Taylor,JR; Hasan,T (Nano Research, 2015)
We fabricate a free-standing few-layer molybdenum disulfide (MoS2)-polymer composite by liquid phase exfoliation of chemically pristine MoS2 crystals and use this to demonstrate a wideband tunable, ultrafast mode-locked fiber laser. Stable, picosecond pulses, tunable from 1,535 nm to 1,565 nm, are generated, corresponding to photon energies below the MoS2 material bandgap. These results contribute to the growing body of work studying the nonlinear optical properties of transition metal dichalcogenides that present new opportunities for ultrafast photonic applications.